Interlocking Directorship in New Zealand - Jamal Roudaki; Md. Borhan Uddin Bhuiyan (Australasian Accounting, Business and Finance Journal, 2015)
The aim of this research is to identify the determinants and consequences of interlocking board membership in New Zealand and whether this interlocking affects the firm performance. This research used a sample of 276 firm years and 1,783 directors from New Zealand listed companies. A two-fold approach analysing the overlap of directors’ names, boards, and company levels was used. This research finds that New Zealand firms are highly interlocked. While concentrated ownership firms react negatively to interlocking, this research finds that interlocking is negatively impacting firm performance in New Zealand. This research also finds that New Zealand firms were significantly interlocked under both approaches, which resulted in negative firm performance. This study has wide application to the New Zealand Financial Market Authority and Institute of Directors New Zealand to evidence the possible effects of directors of being involved (“busy”) in more than one company at the same time. This is the first paper on firm and board interlocking based on New Zealand stock exchange data following the corporate governance best practice code 2004 regime which identified both the determinants and consequences of interlocking.
Keywords: board independence; CEO interlock; interlocking director; interlocked company; firm performance; New Zealand